Modeling and performance analysis of nuclear-renewable micro hybrid energy system based on different coupling methods. (November 2020) - Abdussami, Muhammad R.; Adham, Md Ibrahim; Gabbar, Hossam A.
Abstract: Resilient operation of medium/large scale off-grid energy systems requires continuous and sustainable energy resources. In this view, a nuclear-renewable integrated system could be a potential energy network. This paper proposes three methods, called Direct Coupling, Single Resource and Multiple products-based Coupling, and Multiple Resources and Multiple products-based Coupling, of hybridization for optimal planning of Nuclear-Renewable Micro Hybrid Energy System (N-R MHES). In N-R MHES, Micro Modular Reactor (MMR) is coupled with Renewable Energy Sources (RESs) to provide a reliable, resilient, and sustainable solution to energy crisis at remote locations. Complex mathematical modeling of N-R MHES, based on distinct proposed hybridization methods, is carried out in this paper. Particle Swarm Optimization (PSO) algorithm is used to achieve optimal system configuration and to assess the effectiveness and performability of different N-R MHESs. The objective of the optimization problem is to obtain the lowest Net Present Cost (NPC). The simulation results show that multiple resources and multiple products-based N-R MHES provides the lowest NPC ( 98.3 million), compared to directly coupled N-R MHES ( 165 million) and single resource and multiple products-based N-R MHES ( 161.02 million), with an acceptable margin of reliability. System reliability is evaluated based on a technical Key Performance Indicator (KPI), named Loss of Power Supply Probability (LPSP). A sensitivity analysis has also been conducted to evaluate the impacts of different economic system parameters on NPC. This research explicitly focuses on the prospect of resilient N-R MHES for off-grid applications.